2016
DOI: 10.12707/riv15026
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent depression in schools: + Contigo Project

Abstract: Background: Adolescent depression is considered a public health issue in Portugal, despite the lack of national epidemiological data. It involves a high degree of mortality, namely by suicide, which is the third leading cause of death in the 15-24 age group. Objectives: To assess the presence and severity of depressive symptoms in a non-clinical population of adolescents. Methodology: This is a quantitative, descriptive and cross-sectional study, using the Portuguese version of the Beck Depression Inventory (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
(30 reference statements)
2
4
1
5
Order By: Relevance
“…Regarding the levels of depressive symptomatology in the present sample, girls presented significantly higher levels of symptomatology compared to boys. Although the magnitude of the means difference was small, these result is consistent with what has been verified in the literature (Cardoso, Rodrigues, & Vilar, 2004;Duarte et al, 2015;Erse et al, 2016;Ferreira, 2016;Gomes et al, 2015).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the levels of depressive symptomatology in the present sample, girls presented significantly higher levels of symptomatology compared to boys. Although the magnitude of the means difference was small, these result is consistent with what has been verified in the literature (Cardoso, Rodrigues, & Vilar, 2004;Duarte et al, 2015;Erse et al, 2016;Ferreira, 2016;Gomes et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…A review made by Costello, Copeland and Angold (2011) revealed an increase in the depression prevalence at the transition from childhood to adolescence, with the onset of depression at the second developmental stage being associated with a relatively stable and more severe course over time, with a greater risk of recurrence. Erse et al (2016) did a review of studies with non-clinical adolescent samples and found that 9.2% to 14% of adolescents suffer from moderate or severe depression, with a higher prevalence among girls.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Brazilian study identified a prevalence of 30.0% of anxiety and depressive disorders in adolescence (6) . A similar result was found in Portugal, which presented an index of 31.2% of adolescents with symptoms of depression (7) .…”
Section: Introductionsupporting
confidence: 82%
“…Parents must give their consent for questionnaire application. In addition to adolescents, the intervention is also targeted at the members of the educational community (Erse et al, 2016;Santos, Simões, Erse, Façanha, & Marques, 2014) …”
Section: The +Contigo Projectmentioning
confidence: 99%